A study of some characteristics of structure, meaning and culture of English idioms about animals - Phạm Thị Tố Như. (Đại học Ngoại ngữ Hà Nội, 1998)
This thesis presents a study of some characteristics of structure, meaning and culture of English idioms about animals.